Analisis Alokasi Anggaran Kegiatan Pembangunan Bidang Drainase pada Dinas PU dan Penataan Ruang Kota Banjarmasin - Erdira, Maulidina Nur; Nur, Muhammad Anshar (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to analyze 1) the criteria that determine the budget allocation for drainage development activities at the Banjarmasin City PUPR Service, 2) Alternative drainage development activities at the Banjarmasin City PUPR Service, 3) Budget allocation preferences for drainage development activities at the Banjarmasin City PUPR Service. Eight respondents in the study are considered influential in determining the budget allocation for drainage development activities at the Department of Public Works and Spatial Planning Banjarmasin using the AHP method. The results of the study show that alternative criteria for HR, Benefits, and Funds can determine the budget allocation for drainage development activities with the highest order of preference, namely Funds (54%), Benefits (29%), and Human Resources (0.17%). Based on these criteria, the preference for budget allocation for drainage development activities is Operation Maintenance of Drainage System (39%), Construction of Environmental Drainage System (24%), Rehabilitation of Urban Drainage Channels (20%), and Improvement of Environmental Drainage Channels (18%). With the conclusion that the most dominant is the Operation and Maintenance of Drainage Systems (39%).